Problem Based Learning Model with TaRL Approach on Reflection Material to Increase High School Students' Learning Motivation - Muri, Nurhafiza; Hasbi, Muh.; Purwanti, Purwanti (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to improve students' learning motivation through the application of the Problem-Based Learning (PBL) learning model with the Teaching at the Right Level (TaRL) approach on reflection material. This study is a Classroom Action Research (CAR), which was carried out in two cycles in class XI.G of High School 4 Palu, with 35 students participating. The main instrument used in this study was a learning motivation questionnaire consisting of five indicators: interest in learning, enthusiasm for learning, responsibility, sincerity in responding to teacher questions, and reactions to stimuli given by the teacher. The results of the study showed an increase in students' learning motivation after the application of the PBL model with the TaRL technique. In Cycle I, the learning motivation of the majority of students was still in the low (57.14%) and moderate (42.86%) categories, with an average motivation score of 47. After the observed improvement in Cycle II, a significant increase occurred, with 54.29% of students reaching the strong motivation category and 45.71% in the moderate category, while the average score increased to 68. The findings indicate that the combination of the PBL model with the TaRL method effectively increases students' learning motivation, particularly through grouping techniques based on cognitive ability levels. Consequently, education tailored to students' needs and abilities can foster a more significant and inspiring learning experience.